Perspective of social media as an organisational KM tool: contemporary literature review - Khalili, Amjad; Abbadi, Ala’; Ismail, Md Yusof (2019)
Organisational knowledge management (KM) has been well comprehended over the past couple of decades as a significant fragment of leading enterprises. Besides, it is deliberated as an integral module of a business organisation. Additionally, globalisation plays a significant role in how business is conducted leading to innovative technological trends. Social media (SM) tools such as blogs, Wikis, and other social networking platforms have taken the world by storm and are no longer a trivial phenomenon. SM has become a mainstream tool enabling people to connect, communicate, collaborate, producing new possibilities and challenges to facilitate easier, faster, and more widespread sharing of information through this energetic, and intricate information infrastructure. This paper reviews relevant literature on business motives for social software adoption, the benefits, related issues and mitigation of the said issues. Further, it critically analyses SM literature and its effects on KM to better understand the effective usage and potential of related tools and how these enhance business environment and sharing knowledge. This paper explored the relationship between national culture and social media enabled KM.